Critical Discourse Study of Online Media News about Cameron Herrin Issues: The Analysis of Van Dijk's Ideological Square - Sundari, Sundari; Irawan, Andi Muhammad (English Language and Literature, 2024)
This research is aimed at finding out, anayzing and classifying (1) the discourse topics) (2) the discourse strategies on the two online news texts 1) Cameron Herrin went to prison for Tampa crash. Were the tweets followed real? 2) Cameron Herrrin: How Privilege Can Make You Get Away with Murder?. In this research, the researcher use qualitative method to analyze and classify the data in the term of written-text by using Van Dijk’s analytical approach of ideological namely positive-self and negative-other presentations. The researcher analysed the discourses presented in several news textt. This study focuses on the attacks that Herrin receives through social media and also what priilege Herrrin has so that many people defend him. From two texts being analysed, the researcher has collected 34 data. By utilizing Van Dijk’s ideological structure, the researcher found out 25 discourse topics implied in ‘Cameron Herrin went to prison for Tampa crash. Were the tweets followed real? And ‘Cameron Herrin: How Privilege Can Make You Get Away with Murder.’ Furthermore, there are 8 discourse strategies in the texts such as victimization, metaphor, hyperbole, repetition, vagueness, euphemism, parallelism, and simile which is most often found in the text ‘Cameron Herrin: How Privilege Can Make You Get Away with Murder’.